Book Illustration as (Intersemiotic) Translation: Pictures Translating Words - Pereira, Nilce (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2008)
AbstractThis article examines book illustrations through the prism of Translation Studies. It mainly suggests that the pictures in illustrated books are (intersemiotic) translations of the text and that, as such, they can be analyzed making use of the same tools applied to verbal interlingual translation. The first section deals with the theoretical bases upon which illustrations can be regarded as translations, concentrating on theories of re-creation, as illustration is viewed essentially as the re-creation of the text in visual form. One of the claims in this section is that, because illustration is carried out in very similar ways as interlingual translation itself, the term “intersemiotic” relates more to the (obvious) difference of medium. For this reason the word is most often referred to in parentheses. The second section discusses three particular ways through which illustrations can translate the text, namely, by reproducing the textual elements literally in the picture, by emphasizing a specific narrative element, and by adapting the pictures to a certain ideology or artistic trend. The example illustrations are extracted from different kinds of publication and media, ranging from Virgil’s Aeneid, Lewis Carroll’s Alice in Wonderland and Mark Twain’s Adventures of Huckleberry Finn to an online comic version of Shakespeare’s Hamlet.